COVID-19 Disease Course in Former Smokers, Smokers and COPD Patients - Alberca, Ricardo Wesley; Lima, Júlia Cataldo; Oliveira, Emily Araujo de; Gozzi-Silva, Sarah Cristina; Ramos, Yasmim Álefe Leuzzi; Andrade, Milena Mary de Souza; Beserra, Danielle Rosa; Oliveira, Luana de Mendonça; Branco, Anna Cláudia Calvielli Castelo; Pietrobon, Anna Julia; Pereira, Nátalli Zanete; Teixeira, Franciane Mouradian Emidio; et al. (Frontiers in Physiology, 2021)
The severe respiratory and systemic disease named coronavirus disease-2019 (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Currently, the COVID-19 pandemic presents a huge social and health challenge worldwide. Many different risk factors are associated with disease severity, such as systemic arterial hypertension, diabetes mellitus, obesity, older age, and other co-infections. Other respiratory diseases such as chronic obstructive pulmonary disease (COPD) and smoking are common comorbidities worldwide. Previous investigations have identified among COVID-19 patients smokers and COPD patients, but recent investigations have questioned the higher risk among these populations. Nevertheless, previous reports failed to isolate smokers and COPD patients without other comorbidities. We performed a longitudinal evaluation of the disease course of smokers, former smokers, and COPD patients with COVID-19 without other comorbidities, from hospitalization to hospital discharge. Although no difference between groups was observed during hospital admission, smokers and COPD patients presented an increase in COVID-19-associated inflammatory markers during the disease course in comparison to non-smokers and former smokers. Our results demonstrated that smoking and COPD are risk factors for severe COVID-19 with possible implications for the ongoing pandemic.